Long-term outcomes following percutaneous coronary intervention (PCI). (3rd May 2023) - Pottle, A; Bellchambers, J; Harrison, N; Harrison, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Outcomes measures following PCI usually focus on in-hospital and 30-day mortality and readmission rates following discharge. There are numerous cardiac registries worldwide but there is a lack of data on longer-term patient-centred outcomes. ESC guidance recommends that patients are re-evaluated at least annually following myocardial revascularisation to reassess symptoms and adherence to secondary prevention measures and reinforce medical therapy and lifestyle changes when appropriate (1C recommendation). The International Consortium for Health Outcome Measures have produced a dataset of recommended outcome measures including long-term follow-up to 5 years and beyond, focusing on aspects of health experience that are important to patients. Real life data on long-term outcomes following PCI is needed in addition to short-term outcome measures to establish patient experience of PCI. Purpose: The study was carried out to evaluate the long-term outcomes of patients undergoing PCI in this tertiary centre. Method: Nurse-led follow-up for all patients post PCI has been carried out since 2001. Outcome data were initially collected prospectively during clinic appointments; short-term at 1-month, and medium-term at 6-months and 1-year. Long-term outcome data at 3 and 5-years were collected from 2012 via telephone appointment or purpose-made questionnaire. Results: Data are available from 3-year follow-up for patients who underwent PCI between 2009 and 2014 and 5-year follow-up from patients between 2007 and 2012. The results only relate to patients followed-up in the nurse-led service. There were 3568 patients followed-up at 3-years and 2088 followed-up at 5-years (total 5656). 59.4% of patients had undergone primary PCI at 3-years and 64.1% at 5-years. 76% of the respondents were male at both time periods. The average age was 75.4 years. The data showed that at 3-years, 45.2% of patients reported they had no chest pain, or no angina on normal activity. At 5-years this number was 48.6%. 80.7% were free of MACE events at 3-years and 78.4% at 5-years. Approximately 50.0% of MACE events were non-cardiac hospitalisations. The number of patients requiring further intervention at both time periods was small. Conclusion: Procedural outcome from PCI is good in the long, as well as short-term. Patient reported outcomes indicate that symptom control is potentially not as good as would be expected. Patients need long-term follow-up with a healthcare professional to establish if reported symptoms are truly cardiac and therefore warrant further investigation, however, healthcare resources may limit the ability to do this.